Brain derived neurotrophic factor and neurotrophin-4 employ different intracellular pathways to modulate norepinephrine uptake and release in rat hypothalamus - Rodríguez Fermepin, Martin (2009)
Classical actions of the neurotrophin family are related to cellular survival anddifferentiation. Moreover, acute effects of neurotrophins have been reported. Althoughneurotrophins effects on synaptic transmission at central nervous system level have beenlargely studied, acute effects of neurotrophins on hypothalamic noradrenergic transmissionare still poorly understood. Thus, we have studied the effects of the neurotrophin familymembers nerve growth factor (NGF), brain derived neurotrophic factor (BDNF) andneurotrophin-4 (NT-4) on norepinephrine (NE) neuronal uptake and its evoked release, aswell as the receptor and the intracellular pathways involved in these processes in rathypothalamus.Present results indicate that BDNF increased NE uptake and decreased its evoked releasethrough a mechanism that involve Trk B receptor and phospholipase C. Moreover, NT-4,also through the Trk B receptor, decreased NE uptake and its evoked release by activatingphosphatidylinositol 3-OH-kinase. These effects were observed in whole hypothalamus aswell as in the anterior hypothalamic zone. On the other hand, NGF did not modifynoradrenergic transmission.In conclusion, we showed for the first time that BDNF and NT-4 activate two differentintracellular signalling pathways through a Trk B receptor dependent mechanism.Furthermore, present findings support the hypothesis that BDNF and NT-4 acutely applied,could be considered as modulators of noradrenergic transmission and thus may regulatehypothalamic physiological as well as pathophysiological responses.